2020
DOI: 10.1002/isd2.12138
|View full text |Cite
|
Sign up to set email alerts
|

Examining the use of electronic money and technology by the diaspora in international remittance system: A case of Somali remittances from Canada

Abstract: The diaspora, particularly through ICT‐enabled remittances, are an important lifeline to many in the developing world. This study aims to better understand the usefulness of ICTs in the role played by the remittance sending diasporans in developing countries' economic and social system. Through a mixed‐method approach, we explore the institution behind the Somali Hawala system and how it is enabled by technology. Guided by the question: What is the role of electronic money, technology, and the diaspora in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…Nevertheless, inChang and Benson (2022) study, "Migration and Financial Transactions: Factors Influencing Mobile Remittance Service Usage in the Pandemic", they examined these problems and discovered that mobile banking services had become essential for the survival of those who received remittances via mobile devices. The study byElmi and Ngwenyama (2020) andMohapatra and Ratha (2011) have similar arguments. TheElmi and Ngwenyama (2020) study drew on social network theory and altruism theory to support their findings that ICTs play a major role in remittances.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Nevertheless, inChang and Benson (2022) study, "Migration and Financial Transactions: Factors Influencing Mobile Remittance Service Usage in the Pandemic", they examined these problems and discovered that mobile banking services had become essential for the survival of those who received remittances via mobile devices. The study byElmi and Ngwenyama (2020) andMohapatra and Ratha (2011) have similar arguments. TheElmi and Ngwenyama (2020) study drew on social network theory and altruism theory to support their findings that ICTs play a major role in remittances.…”
supporting
confidence: 55%
“…The study byElmi and Ngwenyama (2020) andMohapatra and Ratha (2011) have similar arguments. TheElmi and Ngwenyama (2020) study drew on social network theory and altruism theory to support their findings that ICTs play a major role in remittances. This report is also in line withYoshino et al (2018) that looked at how using internet services to send remittances impact on the reduction of the poverty gap ratio in Asia.In Nigeria, empirical research on the topic, such asTayo et al (2016) investigation into the experiences and opinions of low-income community members who volunteered to take part in the study, found that factors such as accessibility to computers and the Internet, exposure to online content, instruction in computer use, advantages for job hunting, and networking are crucial to the enhancement of the welfare of households in a digital era.…”
supporting
confidence: 55%
“…With the exclusion of individuals who are forced to migrate due to conflict, some economists have traditionally seen immigration as predominantly driven by individual choices [55]. Members of the New Economics of Labor Migration (NELM), a Neo-Classical economics group cited in [56][57][58], pointed out that the family unit is the primary driver of migration. The Members of NELM further believe that past research has frequently overlooked the impact of migration on the country of origin.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Pertukaran tenaga kerja di antara negara satu dengan negara lain adalah sistem kerja sama dalam penyaluran sumber daya manusia dan teknologi demi mencapai aspek kualitas pembangunan (Nwaogu & Ryan, 2015). Tenaga kerja yang bekerja di negara lain mendapatkan hasil dan upah pembayaran selama bekerja, hal inilah yang dapat dijelaskan pada proses pengiriman kas uang yang berasal dari migran ke negara asal memberikan dampak devisa bagi kas negara atau disebut juga sebagai remitansi (Elmi & Ngwenyama, 2020).…”
Section: Remitansiunclassified